ERASMUS + FAB project consortium meeting - UiTM, UiTM Global (Office of International Affairs (OIA), 2024)
The recent Erasmus+ FAB Project Consortium Meeting which convened on January 31, marked a pivotal moment in international collaboration in education and research. Hosted over two days at the Perpustakaan Tun Abdul Razak (PTAR) UITM Samarahan Campus 2 in Sarawak, the meeting was organized by the Department of International Affairs UiTM Sarawak under the guidance of Prof. Dr. Ling Siew Eng and Dr. Wan Juliana Emeih Wahed, Coordinator of DIA. The meeting facilitated fruitful exchanges among representatives hailing from 22 esteemed institutions and organizations across Europe and Asia. This hybrid meeting seamlessly integrated physical participation at PTAR Sarawak with virtual attendance via Zoom Meeting. enhancing accessibility and engagement. Noteworthy attendees included the Ministry of Education Youth and Sport, Cambodia, Cambodian University for Specialties, Build Bright University, University of Aegean, University of Heng Samrin Thbongkhmum, Royal University of Phnom Penh, West Visayas State University, Pokhara University, Nepal, Bangladesh Agricultural University, National University of Management, Cambodia. Ateneo de Manila University, Chea Sim University of Kamchaymear, Shahjalal University of Science and Technology, Mitropolitiko College Anoymi Ekpaideytiki Etairia, and Royal University of Bhutan (RUB-GCBS). The collaborative spirit and in-depth discussions held during the meeting are poised to make a significant impact on the advancement of international education and research endeavors, ultimately benefiting UiTM and the broader Sarawak community.